Computationally-Friendly Argumentation Schemes - Keplicz, Barbara Dunin; Strachocka, Alina (2014 IEEE/WIC/ACM International Joint Conferences on Web Intelligence (WI) and Intelligent Agent Technologies (IAT), 2014)
In an agent activity both paradigmatic aspects of communication and reasoning can be naturally enriched by argumentation. The contribution of this research is a computationally-friendly framework for formalizing paraconsistent argumentation schemes in information-rich environments. This goal is achieved by extending agent's reasoning capabilities with non-deductive methods like argumentation skills. We provide a~generic paraconsistent program template permitting for implementation of various argumentation schemes. To do this, we appeal to techniques specific for the~four-valued framework of 4ql, the~rule-based, dlognneg-like query language. Although dealing with paraconsistency in argumentation schemes is not a new subject, our computational approach takes advantage of the tractability of 4ql. The paper concludes with an example of the Expert Opinion scheme implemented in 4ql.